Christian Empowerment and Secularity - Domsgen, Michael (Ecclesial Futures, 2025)
This paper explores the challenges facing Christian churches in Germany amid increasing secularization and societal change. Key issues include the loss of institutional self-evidence, financial instability due to declining church membership, and the erosion of trust following abuse scandals. In response, the concept of empowerment is examined as a theological and pedagogical approach to fostering individual and communal agency. Drawing from interdisciplinary perspectives in community psychology, social work, disability studies and critical pedagogy, the study highlights how empowerment can create new pathways for engaging with the Christian message. Research at the CES focuses on religious communication, missional church development, and church theory in secular contexts, aiming to enhance the relevance of the Gospel through empowerment-driven approaches.